The role of self-criticism in the relationship between infertility-related stress and anxiety and depression symptoms in women facing [comunicação oral] - Pedro, Juliana (2023)
Infertility is a demanding and stress-inducing medical condition, wich can trigger anxiety and depression symptoms in women. [...]